Design characterization of multiport electro-optical circuits for broadband voltage measurements in an electromagnetically polluted environment : doctoral thesis - Štimac, Hrvoje (H. Štimac; Faculty of electrical engineering and computing, 2020)
Broadband electro-optical differential probes for voltage measurements in an electromagnetically polluted environment are designed and characterized. The differential circuit topology is used because of its good immunity to noise. By separating the signal acquisition and signal processing part of the system, a fully isolated measurement system is implemented, where both the measured RF signal and the bias signal are transmitted using an optical connection. The probe circuit consists of the attenuator, the laser, and the bias circuit. Each part of the probe circuit is characterized by performing measurements, electromagnetic and circuit simulations, and circuit modelling. The simple and low cost measurement system is designed for characterization of electrostatic discharge waveforms. Scientific contribution of the doctoral thesis: 1. Methodology combining admittance parameters and mixed-mode scattering parameters for modelling electro-optical devices and for characterizing differential-mode and common-mode response. 2. Differential electro-optical equivalent circuit model of a vertical-cavity surface-emitting laser for common-mode rejection ratio estimation. 3. Design and characterization of multiport broadband electro-optical differential probes for voltage measurements in an electromagnetically polluted environment. 4. Comparative analysis of the floating-ground and connected-ground differential electro-optical voltage probes operating in GHz-range.